2008
DOI: 10.1002/jso.20989
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P53, P27 and KI‐67 in colorectal cancer patients of various ethnic origins: Clinical and tissue microarray based analysis

Abstract: Ethnicity among Ashkenazi and SJ and PA appears to have a significant impact on disease outcome in patients with CRC patients, while primary tumor expression of p53, p27 and Ki-67 was unrelated to disease outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…We also found that dMMR/MSI-H was not associated with Ki-67 expression, which is in keeping with the view that the expression of Ki-67 did not correlate with CRC biological behavior and prognosis. 48,49 Additionally, our data also showed that MSI-H was significantly associated with TNM stage II. Several studies demonstrated that 5-FU-based adjuvant chemotherapy not only was invalid but it might also have a detrimental impact on survival in stage II MSI-H CRC patients.…”
Section: Discussionsupporting
confidence: 68%
“…We also found that dMMR/MSI-H was not associated with Ki-67 expression, which is in keeping with the view that the expression of Ki-67 did not correlate with CRC biological behavior and prognosis. 48,49 Additionally, our data also showed that MSI-H was significantly associated with TNM stage II. Several studies demonstrated that 5-FU-based adjuvant chemotherapy not only was invalid but it might also have a detrimental impact on survival in stage II MSI-H CRC patients.…”
Section: Discussionsupporting
confidence: 68%
“…TMA blocks were cut to 5-µm sections and deparaffinized, rehydrated in graded alcohol, and processed. 17 Antibodies were used to recognize CD3 (F7.2.38, Dako, Carpinteria, CA), CD8 (c8/144B, Dako), CD4 (polyclonal goat, R&D Systems, Minneapolis, MN), and FoxP3 (236A/E7, Abcam Inc., Cambridge, MA). Biotinylated secondary immunoglobulins were added (Vector Laboratories, Inc., Burlingame, CA) followed by avidinbiotin peroxidase complexes (1:25; Vector Laboratories, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…After review of the archived primary tumour haematoxylin and eosin (H&E) slides and diagnostic confirmation, sections were deparaffinized, rehydrated in graded alcohol, and processed as previously described 23 . Monoclonal antibodies were used to detect CD3 (F7.2.38; Dako North America, Inc., Carpinteria, CA, USA), CD8 (c8/144B; Dako North America, Inc.), FoxP3 (236A/E7; Abcam, Inc., Cambridge, MA, USA) and CD4 (polyclonal goat; R&D Systems, Inc., Minneapolis, MN, USA).…”
Section: Methodsmentioning
confidence: 99%